Reducing Technical and Non-Technical Losses in the Power Sector - Antmann, Pedro (World Bank, Washington, DC, 2014)
This document reviews experience with efforts in developing countries by private as well as state-owned electricity companies to reduce total losses in transmission and distribution and provides examples of sustainable reductions.